2008
DOI: 10.1007/s00056-008-0741-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Sealant

Abstract: Our results demonstrate that Light Bond Reliance, the viscous sealant used in this study, may assist in preventing or reducing the incidence of enamel demineralization. We also noted a correlation between the sealant's use and the incidence of bracket loss in the treatment group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Thirteen were RCTs, out of which, where 11 studies used the split-mouth design and the other two a parallel-arm design 23 , 39 . Eleven of the included studies were non-RCTs, out of which 9 studies used the split-mouth design and the other 2 a parallel-arm design 27 , 40 . Eventually, 1117 patients (age range: 11–40 years) with at least 12,809 teeth being treated were included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen were RCTs, out of which, where 11 studies used the split-mouth design and the other two a parallel-arm design 23 , 39 . Eleven of the included studies were non-RCTs, out of which 9 studies used the split-mouth design and the other 2 a parallel-arm design 27 , 40 . Eventually, 1117 patients (age range: 11–40 years) with at least 12,809 teeth being treated were included.…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, 1117 patients (age range: 11–40 years) with at least 12,809 teeth being treated were included. Unfortunately, the exact number of treated teeth were not reported in 4 studies 23 , 27 , 41 , 42 . Overall, 34 different coating materials have been analysed (Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An undesirable effect of Class II elastics is the protrusion of the lower anterior teeth as the force is concentrated on the lower anterior segment. This can, however, be prevented by using a pre-torqued wire prior to wearing Class II elastics or using brackets with built-in labial root torque [26,27]. Most of the authors have shown that the use of Class II elastics has predominant dentoalveolar effects (e.g.…”
Section: Resultsmentioning
confidence: 99%